Representasi Relasi Kuasa Dalam Kelompok Masyarakat Pada Film Tilik - Fairuz Arta Abhipraya; Muhammad Iqbal Khatami; Muhammad Hima El Muntaha (UMSU, 2021)
This article will explain the representation of power relations over information conducted in social groups which contains group of mothers in a short movie titled Tilik. This article is communication research, because the representation of power relations presented in this short movie can be constructed through scenes in the form of signs that can also be interpreted and analysis. The problem formulation in this article is how the representation of power relations in the short film titled Tilik? Researcher use some literature review in this article such as about representations, power relations over information, and constructiveness in movie, movie as social realities, characters in movie sections, and political agendas depicted in movie. The method used to analysis in this research is Vladimir Propp's narrative method and Michel Foucault's theory of power relations. The power relation that is presented in this short movie is the power over the information that is owned by Bu Tejo to the social groups of mothers who are involved in the movie, this is shown by several parts of the movie that were deliberately selected by the researcher as material for analysis. This study resulted in the conclusion that the representation of power relations is held dominantly by Bu Tejo, because Bu Tejo had information that is not owned by other social groups of mothers. On the other hand, Bu Tejo's power relationship is useful for strengthening social ties and garnering electoral support for her husband in the upcoming local head of village election.